2012
DOI: 10.1021/bi300645n
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Bis-benzimidazoles Are Potent Anti-Staphylococcal Agents with Dual Inhibitory Mechanisms against DNA Gyrase

Abstract: Various bis-benzimidazole derivatives have been reported to possess activity against Gram-positive pathogens. No mechanism of action has been elucidated to fully account for the antibacterial activity of this class of compounds. A group of symmetric bis-benzimidazoles (BBZ) designed as anticancer agents have previously been shown to possess moderate antiproliferative activity. We sought to assess the antibacterial activity and mechanism of action of BBZ compounds against Staphylococcus aureus. Antibacterial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…The topoisomerases modulate the supercoiling of DNA to enable proper function and interaction with proteins. These enzymes also have a fundamental role in most nucleic acid processes, like helping to control levels of DNA under- and over-winding, as well as removing knots and tangles from bacterial chromosomes [71,72,73]. The enzymes that cleave just one strand of the DNA are called type I topoisomerases, and they are further divided into type IA, based on the protein covalent linkage to 5′-phosphate, or type IB if the linkage is to 3′ phosphate of the DNA strand.…”
Section: Targets Of Quinolonesmentioning
confidence: 99%
“…The topoisomerases modulate the supercoiling of DNA to enable proper function and interaction with proteins. These enzymes also have a fundamental role in most nucleic acid processes, like helping to control levels of DNA under- and over-winding, as well as removing knots and tangles from bacterial chromosomes [71,72,73]. The enzymes that cleave just one strand of the DNA are called type I topoisomerases, and they are further divided into type IA, based on the protein covalent linkage to 5′-phosphate, or type IB if the linkage is to 3′ phosphate of the DNA strand.…”
Section: Targets Of Quinolonesmentioning
confidence: 99%
“…The bis-benzimidazoles usually exert their activity by their capacity to inhibit topoisomerase IV andD NA gyrase (topoisomerase II) in Gram-positive bacteria. [45] Among them, compounds 63-65 were found to possess not only potent activity against two vancomycin-intermediate S. aureus (VISA) strains, methicillinsusceptible S. aureus,a nd al arge collection of MRSA isolates with MIC values of 1 mgmL À1 ,b ut also good activity against S. pyogenes, S. agalactiae,a nd Group Hs treptococci. Compound 63 also showed strong activity against S. pneumoniae, with an MIC 50 value of 0.06 mgmL À1 .I np articular,c ompound 65 was the most active against the above strains.AS AR study indicated that the terminal functional group on the phenyl ring and its position plays an important role in determining the overall antibacterial activity.F or example, repositioningt he methoxyg roup from the meta to the para position yielded compound 65 with substantial activity.M oreover, para-amino groups (compound 64)c onferreds trong anti-MRSA activity.…”
Section: Bis-benzimidazole Compoundsmentioning
confidence: 99%
“…He showed that BBZs, in common with many conventional, clinically indispensable antibiotics, have a complex, multifactorial antibacterial mechanism which includes the capacity to inhibit the binding of DNA gyrase to DNA and to promote the accumulation of single-stranded DNA breaks. 24 …”
Section: Microbiological Studiesmentioning
confidence: 99%
“…He showed that BBZs, in common with many conventional, clinically indispensable antibiotics, have a complex, multifactorial antibacterial mechanism which includes the capacity to inhibit the binding of DNA gyrase to DNA and to promote the accumulation of single-stranded DNA breaks. 24 Of particular interest was the relatively strong and previously unreported activity of several BBZs against Mycobacterium tuberculosis (Mtb); this was manifest against both the standard laboratory Mtb strain H37RV and 10:104, a recently isolated drug-hetero-resistant Mtb bacterium. Further, the compounds were active against logarithmic phase cultures and latent cultures induced by hypoxia.…”
Section: Microbiological Studiesmentioning
confidence: 99%